An abstract nonlocal second order evolution problem - Ludwik Byszewski; Teresa Winiarska (Opuscula Mathematica, 2012)
The aim of the paper is to prove theorems on the existence and uniqueness of mild and classical solutions of a semilinear evolution second order equation together with nonlocal conditions. The theory of strongly continuous cosine families of linear operators in a Banach space is applied.